2009
DOI: 10.5194/essdd-2-579-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The CARINA data synthesis project: introduction and overview

Abstract: Abstract. The original goal of the CARINA (Carbon in Atlantic Ocean) data synthesis project was to create a merged calibrated data set from open ocean subsurface measurements by European scientists that would be generally useful for biogeochemical investigations in the North Atlantic and in particular, studies involving the carbon system. Over time the geographic extent expanded to include the entire Atlantic, the Arctic and the Southern Ocean and the international collaboration broadened significantly. In thi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
120
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(120 citation statements)
references
References 47 publications
0
120
0
Order By: Relevance
“…This requires estimates of preformed alkalinity, Alk 0 , and these were obtained from salinity using the relationships specifically determined for the Nordic seas by Nondal et al [2009]. Preformed silicate and phosphate was set to 8 and 1 mmol kg −1 , respectively, typical concentrations of Nordic seas surface water in winter as determined from the CARINA data set [Key et al, 2010;Olafsson and Olsen, 2009]. The CO 2 system calculations were carried out using CO2sys [Lewis and Wallace, 1998] for Matlab [van Heuven et al, 2009] using the constants of Mehrbach et al [1973] refit by Dickson and Millero [1987].…”
Section: Ttd Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This requires estimates of preformed alkalinity, Alk 0 , and these were obtained from salinity using the relationships specifically determined for the Nordic seas by Nondal et al [2009]. Preformed silicate and phosphate was set to 8 and 1 mmol kg −1 , respectively, typical concentrations of Nordic seas surface water in winter as determined from the CARINA data set [Key et al, 2010;Olafsson and Olsen, 2009]. The CO 2 system calculations were carried out using CO2sys [Lewis and Wallace, 1998] for Matlab [van Heuven et al, 2009] using the constants of Mehrbach et al [1973] refit by Dickson and Millero [1987].…”
Section: Ttd Methodsmentioning
confidence: 99%
“…Oxygen and CFC data were all obtained with a precision of ∼1% . The data from the three cruises are included in the CARINA data synthesis product [Key et al, 2010] and they have been found to be internally consistent [Falck and Olsen, 2010;Jeansson et al, 2010;Olsen et al, 2009;Olsen, 2009aOlsen, , 2009b, except the CFC-12 data obtained at the G.O. Sars cruise, which should be adjusted by a factor of 0.95 [Jeansson et al, 2010].…”
Section: Datamentioning
confidence: 99%
“…Calculated or interpolated values have been given the quality flag "0". A more comprehensive description of the complete CARINA database can be found in Key et al (2010), as well as in the other, more specialised, papers in this special issue, which includes the paper describing the oxygen data from the Atlantic Ocean region of CARINA (Stendardo et al, 2009). …”
Section: Data Coverage and Parameter Measuredmentioning
confidence: 99%
“…During the project, both primary and secondary quality control (QC) of the data has been performed. A comprehensive description of the complete CARINA data base can be found in Key et al (2009) as well as the other, more specialized, papers in this special issue. An overview of the Atlantic Ocean part of CARINA (CARINA-ATL) is given by Tanhua et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…The second part of CARINA is the merged data files. These are files with all the CARINA data and include: Interpolated values for nutrients, oxygen and salinity if those data are missing and if interpolation can be made according to criteria described in Key et al (2009); Calculated carbon parameters (e.g. if TCO 2 and alkalinity was measured, pH can be calculated).…”
Section: Introductionmentioning
confidence: 99%